Memory and autobiography : explorations at the limits - Arfuch, Leonor; MacSweeney, Christina (Newark, UK : Polity Press, 2020)
"A leading Argentinian scholar examines the role of biography and autobiography in contemporary culture"--
"Originally published in Spanish as Memoria y autobiografia: Exploraciones en los límites © Fondo de Cultura Económica de Argentina, 2013"
Includes bibliographical references (pages [145]-155) and index (p. [156]-166).
Keywords: Autobiography; Biography as a literary form; Biography in art; Memory (Philosophy).